Design, Synthesis And Characterization Of 4-Oxobutanoic Acid Analogues As Potential Human Hypoxia Inducible Factor (Hif) Prolyl Hydroxylase Domain 2 (Phd-2) Inhibitors - Chong, Mui Phin (2018)
There is a widespread interest in developing the human hypoxia inducible factor (HIF) prolyl hydroxylase inhibitors for the treatment of ischemic/hypoxic diseases. In this study, a new series of 4-oxobutanoic acid analogues was investigated as potential HIF prolyl hydroxylase domain-2 (PHD-2) inhibitors. The compounds were designed based on their binding capabilities to the PHD-2 active sites in a bidentate manner, with the most favorable binding modes in the molecular docking studies using Autodock 4.0 and Accelrys Discovery Studio 4.0. The compounds were synthesized by reacting amines and sulfonamides with succinic anhydride. The synthesized compounds were further characterized using 1D-NMR (1H, 13C), 2D-NMR (COSY, HSQC and HMBC), FTIR, CHN elemental analysis and DIMS. PHD-2 RapidFire assay was further employed to determine the in vitro inhibitory potencies of the 4-oxobutanoic acid analogues against PHD-2. The assay results revealed that compounds F2a and F2b were potent PHD-2 inhibitors, with IC50 values of 242 nM and 160 nM, respectively followed by F3a with IC50 value of 71.2μM. F2a and F2b were found to be more potent in inhibiting PHD-2 than the positive control in the assay, FibroGen’s candidate FG-4592 which is undergoing clinical third phase in treating anemia in patient with chronic kidney disease (CKD).